The atmospheric connection between the Arctic and Eurasia is underestimated in simulations with prescribed sea ice - Yu, Qikai; Wu, Bingyi; Zhang, Wenqing (Communications earth & environment, 2024)
Numerous analyses have demonstrated the impact of Arctic sea ice loss on Eurasia during wintertime. However, dynamical models inconsistently support the observed Arctic-Eurasia connection. The critical physical processes causing discrepancies remain unclear. Here, through numerical simulation, we found that the Arctic-Eurasian connection is underestimated when the model is forced with prescribed sea ice concentrations. The suppressed turbulent heat flux over the Arctic sea ice surface, due to the oversimplified sea ice states, is likely an important physical process leading to model spread. By incorporating the reanalyzed turbulent heat flux into the model, we enhance the heat transfer and reproduce the Arctic-Eurasian connection. The weakened Siberian Storm Track and reduced baroclinicity favors the strengthened Siberian High through eddy feedback forcing. These findings highlight the vital role of turbulent heat flux related to sea ice loss, emphasizing the urgent need for enhanced model fidelity in representing the sea ice processes.Incorporating turbulent heat fluxes from reanalysis data in numerical simulations of Arctic sea ice loss enhances heat transfer and reproduces the Arctic-Eurasian connection, despite underestimation in models with prescribed sea ice concentrations, according to results from numerical simulations of sea ice forcing experiments.